Transparency and transferability of learning outcomes : expert assessments on the influence of EU policy initiatives at national level - Symeonidis, Vasileios [Verfasser]; Azzarà, Zelda [Verfasser] (My University, 2025)
„Building a European Education Area requires a seamless and connected learning landscape that enables mobility and lifelong learning for all. Over the past two decades, European countries have made significant efforts in this regard by adopting a learning outcome approach in vocational education and training (VET) and education and training more broadly. This shift has been driven by the need to improve the transparency and transferability of qualifications. This article presents the results of a Cedefop study on the current state of progress.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2 Europa; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; 370; EU-Bildungspolitik; Europäischer Bildungsraum; Lebenslanges Lernen; Lernergebnisorientierung; Europäisches Leistungspunktesystem; Transparenz; Anerkennung